1988
DOI: 10.1093/clinchem/34.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Four assay methods for glycated hemoglobin compared as screening tests for diabetes mellitus: the Islington Diabetes Survey.

Abstract: We assessed the utility of four methods of glycated hemoglobin assay (agar gel electrophoresis with Schiff base, agar gel electrophoresis with prior removal of Schiff base, boronate affinity chromatography, and isoelectric focusing) as screening tests for diabetes mellitus, studying 223 subjects undergoing an oral glucose-tolerance test after fasting and 2 h after ingestion of 75 g of glucose. Assessment of glucose tolerance status according to the 1980 World Health Organization diagnostic criteria indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…10 There are, however, considerable differences between the levels of diagnostic sensitivity and specificity reported for glycated haemoglobin in the literature. In our study, and in others, [11][12][13] HbA 1c was not as sensitive at high specificity as has been claimed elsewhere. 14 These differences may, in part, be attributable to glycated haemoglobin method differences, but most of the available evidence suggests that glycated haemoglobin is slightly less sensitive than FPG for diagnostic purposes.…”
Section: Discussionsupporting
confidence: 62%
“…10 There are, however, considerable differences between the levels of diagnostic sensitivity and specificity reported for glycated haemoglobin in the literature. In our study, and in others, [11][12][13] HbA 1c was not as sensitive at high specificity as has been claimed elsewhere. 14 These differences may, in part, be attributable to glycated haemoglobin method differences, but most of the available evidence suggests that glycated haemoglobin is slightly less sensitive than FPG for diagnostic purposes.…”
Section: Discussionsupporting
confidence: 62%
“…We found that glycated haemoglobin assay imprecision and the variability of the glucose tolerance test [31][32][33] were not the major determinants of the poor relationship. Glycated haemoglobin levels measured by all assay methods showed a considerable range in our study sample [14], probably as a result of the heterogeneity of the population, for example in terms of age, ethnic origin and social class, and thus high and low glycators may demonstrate differences of levels of glycated haemoglobin of 1-2% at the same degree of glucose intolerance (Fig. 1).…”
Section: Discussionmentioning
confidence: 73%
“…Our own observations confirm the previous finding [28] that levels of glycated haemoglobin are stable over this period of time. The withinand between-assay coefficients of variation of these assays on ten replicate samples have been reported [14]. Haemoglobin levels were measured colorimetrically on an EDTA sample using a Coulter haemoglobinometer (Coulter Electronics Ltd., Luton, Bedfordshire, UK) [29].…”
Section: Assay Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 This labile fraction was a nuisance as it reflected short term concentrations in glucose and its presence could confound the interpretation of HbA1c as an estimate of long-term MBG. [15][16][17][18] Taking advantage of its unstable nature, methods to remove this labile fraction such as pre-incubating samples in low pH and/or glucose-free buffers were introduced so as to measure the stable form of HbA1c alone. 15,16,[18][19][20] Other than its role confounding measurement of HbA1c, identifying and interpretation of labile HbA1c has been of passing clinical interest.…”
Section: Introductionmentioning
confidence: 99%